2021
DOI: 10.14710/jbtr.v7i2.11624
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Non-Alcoholic Fatty Liver Disease (NAFLD) fibrosis score (NFS) with Left Ventricular Mass Index (LVMI) in patients with NAFLD

Abstract: Background: Cardiovascular-related mortality is a major concern in NAFLD. Advanced fibrosis was known to be associated with cardiovascular diseases. NAFLD Fibrosis Score (NFS) is used to identify the development of liver fibrosis in NAFLD patients. Left ventricular mass index (LVMI) is a sign of subclinical cardiovascular complications in NAFLD. The correlation between NAFLD fibrosis score with LVMI in NAFLD patients is not fully established.Objective: To analyze the correlation between NAFLD fibrosis score wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In Indonesia, Rahmatullah et al found that men dominated NAFLD sufferers aged between 55 ± 10 years. [14] However, another study conducted by Roberts et al (2021) in Australia showed different results…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In Indonesia, Rahmatullah et al found that men dominated NAFLD sufferers aged between 55 ± 10 years. [14] However, another study conducted by Roberts et al (2021) in Australia showed different results…”
Section: Discussionmentioning
confidence: 96%
“…This relationship makes NAFLD be referred to as the "liver manifestation of metabolic syndrome". [14][23] [24] The patients involved in the study had suffered from DM on average for 6,84 years. In this study, subjects who suffered from NAFLD based on abdominal ultrasound as many as 80 patients, where the most obtained were patients with NAFLD degree I, namely as many as 32 patients (40%), then followed by NAFLD degree II as many as 29 patients (36,3%) and degree stated that the prevalence of NAFLD varied according to five diagnostic procedures: biopsy (51,4%), ultrasound (30,3%), computed tomography (22,9%), Fatty Liver Index (FLI, 20,0%), and fibroscan (52,5%).…”
Section: Discussionmentioning
confidence: 99%